PENGARUH KREDIT BERMASALAH TERHADAP KINERJA KEUANGAN BPR CHRISTA JAYA PERDANA KUPANG - Juwita Leslsy Claudia Adu; Wehelmina M. Ndoen; Reyner F. Makatita (Journal of Management Small and Medium Enterprises (SMEs), 2017)
The purpose of this study is to determine the influence of Nonperforming Loans to Liquidity, toSolvability and to Profitability. This research is descriptive quantitative. Data analysis technique isFinancial Ratio Analysis. The results of this study 1) Non Performing Loan (NPL) at BPR ChristaJaya Perdana Kupang in 2013-2016 of 8.27% is ranked 4 with the predicate "Less Good". 2) LDRBPR Christa Jaya Perdana Kupang in 2013-2016 of 87.85% is ranked 3 with the predicate "GoodEnough". 3) CAR BPR Christa Jaya Perdana Kupang in 2013-2016 of 19.27% is ranked 1 withthe title of "Very Good". 4) ROA BPR Christa Jaya Perdana Kupang in 2013-2016 of 2.6% isranked 1 with the predicate "Very Good". 5) Non Performing Loan (NPL) affects the FinancialPerformance of LDR, CAR and ROA. This indicates that the lower the NPL, the better the LDR,CAR, and ROA of a bankKeywords : Non Performing Loan, Loan to Deposit Ratio, Capital Adequacy Ratio, Return OnAsset.